Viés atencional em faces emocionais no transtorno de personalidade borderline - Vivian, Fabielle Antunes (2020)
Borderline personality disorder is defined by a high emotional instability, which leads to a pattern of impulsive behavior, distorted self-image and, mainly, unstable interpersonal relationships. Attentional bias is a particular way for each person to process certain stimuli at the expense of others, according to the value that is given to them. VA has been extensively studied in cases of anxiety and depression, but little is known about VA in BPD. Seeking to contribute to the elucidation of the attentional bias towards emotional faces in people with BPD, two studies were carried out in this dissertation: a theoretical and an empirical study. The theoretical study aimed to better understand the attentional bias in the TPB from facial stimuli through an integrative literature review. The methodology used was an integrative literature review, in which a search was made for articles accepted or accepted or published in the Scopus, PubMed and PsycNet databases, which were empirical and were in Portuguese, English or Spanish. Results: 17 articles were found, but after the selection steps, seven articles were included in the review. The results of this integrative literature review show that there are few studies in the area that indicate some type of VA in the face of emotional faces, but results are inconclusive, with controversies under what would it be the direction of the VA and in which types of facial expressions. From these few findings on the subject, the empirical study aimed to investigate the VA in emotional faces in people with BPD in the dot-probe task, using the eye tracking device. Method: The sample consisted of n = 25 participants, who were divided into two groups: clinical group (n = 12), who were people with borderine personality traits and control group (n = 13) who were participants with symptoms of depression , without traces of TPB that responded to a dot-probe task with emotional faces (neutral, happy, angry and sad) in the times of 250ms and 1000ms. Results: There were group differences in reaction time for the emotional face of anger in 250ms, and the clinical group was faster to respond to the trials than the control group. Regarding the time taken to fix the gaze analyzed through eye tracking, there were differences in groups as well, indicating that depressed people looked more into the eyes of neutral faces than the group of people with BPD. Conclusions: Study suggests that there is a VA for emotional faces of anger in people with BPD at a more automatic processing stage. Based on this finding, therapeutic interventions focused on BPD are necessary. Future research should continue to study VA in TPB in order to better clarify this process.